Formulasi Dan Evaluasi Sediaan Gel Ekstrak Daun Bidara (Ziziphus Mauritiana Lam) Dengan Basis Viskolam - Maesaroh Adi Galih Sya; Trie Yuni Elfasyari; Yunisa Friscia Yusri (Journal Pharma Saintika, 2021)
. Bidara (Ziziphus mauritiana Lam) is one of the plant in Indonesia that is useful as an antioxidant and anti-inflammatory. Some references also state that bidara leaves are useful as sunscreen. Viscolam is a type of gelling agent with good stability. This study is an experimental study, aimed at determining the effect of variations in viscolam base concentration with the addition of angel leaf ethanol extract on the physical properties of the gel. The gel preparation is made with a variation of 4% (F1) viscolam base;4.5% (F2); and 5% (F3). Bidara leaf extract added to each formulation is as much as 2.5%. The bidara leaf extract gel preparation that has been made is evaluated for the physical properties of the gel in the form of organoleptic test, homogeneity, pH, dispersion, and viscosity of the gel for 21 days, irritation tests and favorability tests. The results stated that the gel preparation was stable and did not cause irritation to the skin and a gel with a viscolam concentration of 5% (F3) was preferred. Further research needs to be done on the antioxidant activity of bidara leaf extract gel with variations in viscolam base to be used as sunscreen preparations.